Stable Overload Management Schemes for Isolated Coupled Microgrids - Pashajavid, Ehsan (Curtin University, 2017)
Enhancing the self-healing capability of the isolated AC microgrids (MGs) through mutual support of neighbouring MGs is the main objective of this thesis. Instead of a back-to-back converter, an instantaneous static switch (ISS) is employed to form a coupled-MG system to avoid the power loss incurred by the converters. The stable schemes for both interconnections of the MGs during overloading and isolation of the coupled MGs when overloading is removed are accurately developed.